Mechanisms Underlying Alcohol-Approach Action Tendencies: The Role of Emotional Primes and Drinking Motives - Cousijn, Janna; Luijten, Maartje; Wiers, Reinout W. (Frontiers in Psychiatry, 2014)
The tendency to approach alcohol-related stimuli is known as the alcohol approach bias and has been related to heavy alcohol use. It is currently unknown whether the alcohol approach bias is more pronounced after emotional priming. The main aim of this study was to investigate whether positive and negative emotional primes would modulate the alcohol approach bias. For this purpose a new contextual Emotional Prime - Approach Avoidance Task (EP-AAT) was developed, containing both negative and positive emotional primes. Explicit coping drinking motives were expected to be related to an increased alcohol approach bias after negative primes. Results of 65 heavy and 50 occasional drinkers showed that the alcohol approach bias was increased in both groups during negative emotional priming. This appeared to be due to slower alcohol avoidance rather than faster alcohol approach. This change in alcohol approach bias was positively related to explicit enhancement drinking motives and negatively related to alcohol use-related problems. A stronger alcohol approach bias in heavy compared to occasional drinkers could not be replicated here and coping drinking motives were not related to the alcohol approach bias in any of the emotional contexts. The current findings suggest that both occasional and heavy drinkers have a selective difficulty to avoid alcohol-related cues in a negative emotional context. Negative reinforcement may therefore be involved in different types of drinking patterns. The influence of emotional primes on alcohol related action tendencies may become smaller when alcohol use becomes more problematic, which is in line with habit accounts of addiction.